PCSK9 Targeting in the Management of Hypercholesterolaemia - Constantine E. Kosmas; Evangelia J. Papakonstantinou; Jacqueline Carreño; Rogers Echavarria Uceta; Eliscer Guzman; Andreas Sourlas (European Medical Journal Cardiology, 2023)
It has long been established that elevated plasma concentrations of low-density lipoprotein cholesterol (LDL-C) are among the prominent contributors leading to the development of atherosclerotic plaques and, ultimately, cardiovascular disease. In the current era of optimal risk factor modification, proprotein convertase subtilisin/kexin type 9 (PCSK9) targeting has emerged as a potent therapeutic approach in the management of hypercholesterolaemia, addressing several substantial, unmet clinical needs. PCSK9 monoclonal antibodies, evolocumab and alirocumab, as well as inclisiran, which is a small interfering RNA that halts the transcription of PCSK9 mRNA, are being increasingly used in current clinical practice, as they induce intensive LDL-C reductions without any significant safety and tolerability concerns. Based on the success of these agents, the concept of PCSK9 targeting with novel agents with enhanced biological properties, or via different administration routes, has received considerable attention. In this regard, numerous antisense oligonucleotides, peptides, and proteins are currently under evaluation in randomised controlled trials, yielding propitious results up to date; they may enter clinical use in the coming years. Meanwhile, a PCSK9 vaccine, as well as genome editing via clustered regularly interspaced palindromic repeats/Cas9, hold great promise to eradicate LDL-C altogether as a cardiovascular risk factor. This review aims to present and discuss the current clinical and scientific evidence pertaining to the field of medications that exert their biological effect by targeting PCSK9, which are either in use in clinical practice, or are currently being evaluated in pre-clinical or clinical studies, and may prove beneficial in the near future.